2022
DOI: 10.1002/ehf2.13871
|View full text |Cite
|
Sign up to set email alerts
|

The first experience with sodium‐glucose cotransporter 2 inhibitor for the treatment of systemic right ventricular failure

Abstract: In congenitally corrected transposition of the great arteries, the morphological right ventricle supports the systemic circulation. This chronic exposure to pressure overload ultimately leads to systemic right ventricular (sRV) dysfunction and heart failure. Pharmacological options for the treatment of sRV failure are poorly defined and no solid recommendations are made in the most recent guidelines. Sodium‐glucose cotransporter 2 (SGLT‐2) inhibitors are a new class of antihyperglycaemic drugs that have been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…121,122 Although some experience in adults with congenital heart disease suggests that sodium-glucose cotransporter-2 inhibitors may be safe and efficacious, even in those with systemic RV, its safety and efficacy among children with congenital heart disease and HF need to be determined. 123,124 Ivabradine SHIFT [Systolic Heart Failure Treatment With the I(f) Inhibitor Ivabradine Trial] demonstrated the efficacy of ivabradine, a sinoatrial node modulator that selectively inhibits the I(f) current, in reducing the composite end point of cardiovascular death or HF hospitalization in adult patients with reduced LVEF. 125 An international randomized multicenter study in children with dilated cardiomyopathy demonstrated an improvement in NT-proBNP, LVEF, and New York Heart Association functional class among ivabradine-treated patients.…”
Section: Sodium-glucose Cotransporter-2 Inhibitorsmentioning
confidence: 99%
“…121,122 Although some experience in adults with congenital heart disease suggests that sodium-glucose cotransporter-2 inhibitors may be safe and efficacious, even in those with systemic RV, its safety and efficacy among children with congenital heart disease and HF need to be determined. 123,124 Ivabradine SHIFT [Systolic Heart Failure Treatment With the I(f) Inhibitor Ivabradine Trial] demonstrated the efficacy of ivabradine, a sinoatrial node modulator that selectively inhibits the I(f) current, in reducing the composite end point of cardiovascular death or HF hospitalization in adult patients with reduced LVEF. 125 An international randomized multicenter study in children with dilated cardiomyopathy demonstrated an improvement in NT-proBNP, LVEF, and New York Heart Association functional class among ivabradine-treated patients.…”
Section: Sodium-glucose Cotransporter-2 Inhibitorsmentioning
confidence: 99%
“…SGLT2 inhibitors also relieve subpulmonic RV pathology and reduce mortality in experimental models of PHTN ( 99 ), suggesting that they might be effective in treating pressure overload-induced sRV dysfunction. A recent case report by Egorova et al was the first published report describing dapagliflozin use in a 28-year-old woman with cc-TGA and NYHA class II-III sRV failure who did not tolerate ARNI therapy ( 100 ). Dapagliflozin use significantly improved the patient’s subjective and objective functional status, similar in magnitude to the ARNI regimen ( 100 ).…”
Section: Management Of the Failing Systemic Right Ventriclementioning
confidence: 99%
“…A recent case report by Egorova et al was the first published report describing dapagliflozin use in a 28-year-old woman with cc-TGA and NYHA class II-III sRV failure who did not tolerate ARNI therapy ( 100 ). Dapagliflozin use significantly improved the patient’s subjective and objective functional status, similar in magnitude to the ARNI regimen ( 100 ). Mechanistic pathways by which SGLT2 inhibitors mitigate cardiac dysfunction may involve decreases in renin-angiotensin-aldosterone system activation and sympathetic outflow ( 101 ).…”
Section: Management Of the Failing Systemic Right Ventriclementioning
confidence: 99%
“…When regarding effects on the RV itself, however, dapagliflozin treatment did not result in any improvements in myocardial function or remodeling ( 162 ). Clinical data on primary RV dysfunction is lacking except for a case report in systemic RV ( 163 ).…”
Section: Current and Future Strategiesmentioning
confidence: 99%